Effect of sodium intake on renin level: Analysis of general population and meta-analysis of randomized controlled trials. (15th July 2016) - Rhee, O.J.; Rhee, M.Y.; Oh, S.W.; Shin, S.J.; Gu, N.; Nah, D.Y.; Kim, S.W.; Lee, J.H.
Abstract: Background: We evaluated the association between sodium intake and plasma renin levels in the cross sectional study and meta-analysis of randomized controlled trials, whether there is a persistent elevation of plasma renin by longer-term sodium intake restriction. Methods: Plasma renin activity (PRA) and 24-h urine sodium (24HUNa) excretion were measured from individuals randomly selected from a community. Simple and multiple linear regression analyses adjusted for age, 24-h systolic blood pressure, 24-h average heart rate, fasting blood glucose and gender were performed. For meta-analysis, 74 studies published from 1975 to mid-2014 were identified in a systematic literature search using EMBASE, CINAHL, and MEDLINE. Random effects meta-analyses and a meta-regression analysis were performed. Results: Among the 496 participants recruited, 210 normotensive and 87 untreated hypertensive subjects were included in the analysis. There was no significant association between PRA and 24HUNa in the total population, or hypertensive and normotensive individuals. In the meta-analysis, the standard mean difference (SMD) of renin level by sodium intake reduction was 1.26 (95% CI: 1.08 to 1.44, Z = 12.80, P < 0.001, I 2 = 87%). In the meta-regression analysis, an increase in a day of intervention was associated with a fall in SMD by − 0.04 (95% CI: − 0.05 to − 0.02, Z = − 5.27, P < 0.001, I 2 = 86%), indicating that longer duration of reduced sodium intake would lead to lesser SMD of renin level. Conclusions: The present population based cross-sectional study and meta-analysis suggests that prolonged reduction in sodium intake is very unlikely associated with elevation of plasma renin levels.